Tensile fatigue properties of carbon fiber reinforced composite orthogonal laminates after moisture absorption - ZHANG Xiang-lin; MENG Qing-chun; XU Ming-rui; ZENG Ben-yin; CHENG Xiao-quan; SUN Wei (Cailiao gongcheng, 2021)
The fatigue performance of composite structures in wet environment will be degraded seriously, which will affect the structure safety. Therefore, the influence of wet environment should be taken into consideration when determining the structure life. The tensile fatigue properties of carbon fiber reinforced composite orthotropic laminates in wet and dry state at room temperature were tested. The influence of saturated moisture absorption on the tensile fatigue properties was studied. The S-N curves of two kinds of environments were obtained. On this basis, the finite element models were established, and the fatigue life and damage evolution of the orthotropic laminate after moisture absorption were predicted. The calculated results agree well with the test results, which prove the validity of the model. The results show that the saturated moisture absorption has a great influence on the tensile fatigue properties of orthogonal laminate. After moisture absorption, the tensile fatigue life of the laminates is significantly lower than that of the laminates in dry state, and the slope of S-N curve is slightly lower. The fiber damage initiation and propagation of laminate are also different from those in dry state.